Mechanism for generating and promoting manufacturing project portfolio synergy - Libiao Bai; Tong Pan; Jieyu Bai; Shuyun Kang; Patrick X.W. Zou (Ain Shams Engineering Journal, 2023)
To explore the mechanism for generating and promoting project portfolio (PP) synergy, a model applying the causal loop diagram (CLD) is established. The efforts have been done include four parts. First, a sustainable objective system is determined through the improved balanced scorecard. Second, three categories of manufacturing projects are identified to illustrate the characteristics and objectives. Third, a CLD model is constructed based on the objective achievement process of PPs. Fourth, suggestions are made to promote the objective realization by synergy. The major result is that the generation and promotion mechanism are portrayed through the causal loops and feedbacks of CLD. CLD is adopted as the analytical approach for superiority in visualizing complex relationships. The main findings are: (1) The synergy generation mechanism is specified that PP synergy generates from the collaborative behaviors among PPs. (2) PP synergy promotes objective realization through additional effects arise from complex feedbacks among behaviors.